The presentation structure of “Lahire Naga Tahun” in Wayang Topeng Malang theatrical dance - Rahayuningtyas, Wida (citeus, 2022)
Dramatari Wayang Topeng shows the diversity of characters, the variety of movements, the diversity of costumes, and the diversity of stories. Dramatari Wayang Topeng show is taken from the Panji story, which is oral literature. 17 stories have been developed by the puppeteers at Padepokan Asmara Bangun, Malang Regency. There is one story that is only performed on certain days, namely the month of Sura, which is the month of reckoning Javanese or Javanese new year, which is entitled Lahire Naga Tahun. The purpose of this research is to describe the presentation structure of